2021
DOI: 10.3390/su13105575
|View full text |Cite
|
Sign up to set email alerts
|

The Climate Change Dilemma: How Cooperation Beliefs Influence Energy Conservation Behavior

Abstract: Despite widespread belief in anthropogenic climate change and high levels of concern about its consequences, behavioral changes necessary to adequately address climate change appear difficult to achieve. This concern–behavior gap is often explained by the public goods character of climate change mitigation, which is associated with a high individual incentive to take a free ride when possible. This paper examines cooperation beliefs and their impact on individuals’ energy conservation behavior. Analyzing data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…A large number of ESS-based studies identified social trust as the key factor explaining the well-known concern-behaviour gap, i.e., the fact that respondents' environmental awareness is not adequately reflected in their actual behaviour. What they find is that pro-environmental behaviour is influenced not only by intrinsic motivation and external economic incentives, but also by how people perceive the likelihood of others' actions (Lübke, 2021). The concern-action relationship is stronger in high-trust countries, while in low-trust countries strong concern is paired with a low level of feeling personal responsibility and climate policy support (Bodor et al, 2020).…”
Section: Individual-level Determinantsmentioning
confidence: 97%
“…A large number of ESS-based studies identified social trust as the key factor explaining the well-known concern-behaviour gap, i.e., the fact that respondents' environmental awareness is not adequately reflected in their actual behaviour. What they find is that pro-environmental behaviour is influenced not only by intrinsic motivation and external economic incentives, but also by how people perceive the likelihood of others' actions (Lübke, 2021). The concern-action relationship is stronger in high-trust countries, while in low-trust countries strong concern is paired with a low level of feeling personal responsibility and climate policy support (Bodor et al, 2020).…”
Section: Individual-level Determinantsmentioning
confidence: 97%
“…Climate protection is a classic collective good problem in the sense that the outcome (1) is desirable for everyone, (2) requires the contribution of as many people as possible, and (3) cannot be protected from free riders [22,23]. The situation that arises can be described as a 'critical collective good situation' [19], (p. 42) or 'social dilemma' [18], in which every individual is better off by not cooperating, yet the individual pay-off decreases if everybody refuses to cooperate [24]. In this setting, self-interested individuals have little reason to act in a way that is beneficial for the collective good because others might not contribute yet reap the rewards of their own efforts.…”
Section: Climate Change Mitigation As a Critical Collective Good Situ...mentioning
confidence: 99%
“…First, there must be some trust in others and in their willingness to cooperate for the collective good, because making sacrifices puts the individual in a vulnerable position and only makes sense if a critical number of others do the same. Therefore, people must have some level of general trust which justifies the assumption that others will, on the one hand, contribute their part [4,18,36] and, on the other hand, offer support to the individual in times of vulnerability and need [37,38]. Second, people need to have trust in the institutions that coordinate collective action and believe that the contributions that political actors ask for will be used effectively and in the common interest.…”
Section: Factors That Promote Support For Climate Change Mitigation M...mentioning
confidence: 99%
See 2 more Smart Citations